Medicina ancestral y turismo de salud de la Comunidad Paratu Yaku, Cantón Francisco de Orellana. - Terreros Caicedo, Kerly Alejandrina (2022)
This research project focuses on "Ancestral medicine and health tourism in the Paratu Yaku community, canton Francisco de Orellana." The following study aims to analyze how ancestral medicine influences health tourism, obtaining information through various tools, techniques, and instruments, in which the dimensions and indicators were determined through the problem tree and complemented with the operationalization of variables, analogically data were acquired through surveys validated by experts. Through Cronbach's Alpha method. The independent variable has an excellent reliability value of 0.965. Therefore, the dependent variable has an acceptable reliability value of 0.771, obtaining hypotheses, conclusions, and recommendations. In effect, the creation of the digital informer of traditional medicine of the Paratu Yaku community is strengthened, in which the characteristics, benefits, and form of use of the plants for consumption are detailed. Finally, we should remember that ancestral medicine is a holistic approach to healing that balances the person's physical, mental and spiritual aspects, an evidence-based practice that has been used successfully for years to heal.